El humor como denuncia social y política: “el gran dictador” de Charles Chaplin - Gladys Graciela González (Cambios y Permanencias, 2016)
The Nazi regime has been recreated from the film over and over again in an attempt to show the horrors that were subjected thousands of people. We analyze the first film that portrayed the figure of Adolf Hitler. This was The Great Dictator, Charles Chaplin, who in 1940 showed the world, from the satiric humor, the engineering of this regime and the weaknesses of the dictator.Our purpose is to know what the humoristic resources that were appealed in the film and explore the possibilities of humor in film as an effective tool for understanding contemporary history were